An Ecological Conceptualization of Extreme Sports - Immonen, Tuomas; Brymer, Eric; Davids, Keith; Liukkonen, Jarmo; Jaakkola, Timo (Frontiers in Psychology, 2018)
Currently, there are various definitions for extreme sports and researchers in the field have been unable to advance a consensus on what exactly constitutes an ‘extreme’ sport. Traditional theory-led explanations, such as edgeworks, sensation seeking and psychoanalysis, have led to inadequate conceptions. These frameworks have failed to capture the depth and nuances of experiences of individuals who refute the notions of risk-taking, adrenaline- and thrill-seeking or death-defiance. Instead, participants are reported to describe experiences as positive, deeply meaningful and life-enhancing. The constant evolution of emerging participation styles and philosophies, expressed within and across distinguishable extreme sport niches, or forms of life, and confusingly dissimilar definitions and explanations, indicate that, to better understand cognitions, perceptions and actions of extreme sport participants, a different level of analysis to traditional approaches needs to be emphasized. This paper develops the claim that a more effective definition, reflecting the phenomenology, and framework of an ecological dynamics rationale, can significantly advance the development of a more comprehensive and nuanced future direction for research and practice. Practical implications of such a rationale include study designs, representative experimental analyses and developments in coaching practices and pedagogical approaches in extreme sports. Our position statement suggests that extreme sports are more effectively defined as emergent forms of action and adventure sports, consisting of an inimitable person-environment relationship with exquisite affordances for ultimate perception and movement experiences, leading to existential reflection and self-actualization as framed by the human form of life.